The Effect of Teacher Caring Behavior and Teacher Praise on Students’ Engagement in EFL Classrooms - Sun, Yadi (Frontiers in Psychology, 2021)
The emergent respect for the prominence of engagement in the present education has made it one of the most widespread inquiry issues that it has been regarded as the ultimate target of learning. In the language teaching field, the idea of student activities for learning is intensely rooted in the prevailing standards of effective language learning, which considers language communication and interaction as analytical for language improvement. Moreover, teachers as center of learning process is the most prominent research attention, and teachers play a key role in regulating the education process as well as students’ learning achievement. However, there is an absence of research which have considered teachers’ care and praise among all positive interpersonal behavior and its significant effect on students’ engagement. So, the present review attempts to focus on teacher care and praise, and their effects on student engagement in EFL classrooms. Subsequently, some implications are presented to clarify the practice of teachers, students, teacher educators, and materials developers.